The Roles of Parathyroid Hormone and Calcitonin in Bone Remodeling: Prospects for Novel Therapeutics - Carter, Percy H.; Schipani, Ernestina (Endocrine, Metabolic & Immune Disorders-Drug Targets, 2006)
Inappropriate regulation of the bone resorption and bone formation processes that occur as a normal part of bone remodeling can lead to net bone loss, as found in osteoporosis. Parathyroid hormone (PTH) and calcitonin (CT) are two peptide hormones that play important roles in calcium homeostasis through their actions on osteoblasts (bone forming cells) and osteoclasts (bone resorbing cells), respectively. Paradoxically, even though genetic deletion of either PTH or CT produces mice with increased bone mass (presumably through different mechanisms), derivatives of both PTH and CT have now been approved for clinical use in the treatment of bone loss in osteoporosis. In this review, we focus on the biology and pharmacology of these two peptides. Specifically, we sequentially address the following three topics in detail: (1) the biological mechanisms of action of PTH and CT, focusing on data from in vitro studies and animal models; (2) the clinical utility of PTH and CT in treating osteoporosis, examining how their pharmacological efficacy correlates with our understanding of their biological mechanism of action; and (3) future prospects for combination therapy, alternative formulation of PTH and CT into oral and transdermal therapies, and replacement of PTH and CT with modified peptides or small molecules. The past four years have witnessed dramatic advances in each of these three areas, and the review places in context the challenges that lie ahead for this complicated, but clinically-relevant field.
Keywords: bone resorbing cells